Brief report: lack of processing bias for the objects other people attend to in 3-year-olds with autism - Falck-Ytter, Terje; Thorup, Emilia; Bölte, Sven (Journal of autism and developmental disorders, 2015)
Whether gaze following - a key component of joint attention - is impaired in children with autism spectrum disorder (ASD) is currently debated. Functional gaze following involves saccading towards the attended rather than unattended targets (accuracy) as well as a subsequent processing bias for attended objects. Using non-invasive eye tracking technology, we show that gaze following accuracy is intact in intellectually low-functioning 3-year-olds with ASD. However, analyses of the duration of first fixations at the objects in the scene revealed markedly weaker initial processing bias for attended objects in children with ASD compared to children with typical development and non-autistic children with developmental delays. Limited processing bias for the objects other people attend to may negatively affect learning opportunities in ASD.